Incomplete risk adjustment and adverse selection in the German public health insurance system; Unvollständiger Risikostrukturausgleich und Adverse Selektion in der Gesetzlichen Krankenversicherung Deutschlands - Thomas Knaus; Robert Nuscheler (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2002)
The German statutory health insurance market was exposed to competition in 1996. To avoid adverse selection, a prospective risk compensation scheme was introduced in 1994. Due to their low contribution rates, company-based sickness funds were able to attract a lot of new members. We analyze – using data from the German Socio- Economic Panel – the determinants of these transitions from 1995 to 2000. By estimating a simultaneous two equation system, we find that health status positively, and significantly, affects the probability of changing to a company-based sickness fund, especially after controlling for age. Thus the risk compensation scheme does not fully control for the health status of the changers. Consequently, the comparative advantages of company-based funds will increase over time. This observation provides evidence for the standard Rothschild-Stiglitz separating equilibrium. – – In der Gesetzlichen Krankenversicherung wurde 1996 Wettbewerb zwischen den Krankenkassen eingeführt. Um Adverse Selektion zu verhindern wurde 1994 ein prospektiver Risikostrukturausgleich eingeführt. Aufgrund ihrer niedrigen Beitragssätze konnten die Betriebskrankenkassen eine Vielzahl neuer Mitglieder gewinnen. Wir nutzen Daten des Sozio-Oekonomischen Panels (SOEP), um diese Wechselbewegungen für den Zeitraum von 1995 bis 2000 zu analysieren. Ein Zweigleichungssystem wird simultan geschätzt. Es zeigt sich, dass der Gesundheitszustand, nachdem insbesondere für Alter kontrolliert wurde, die Wahrscheinlichkeit zu einer Betriebskrankenkasse zu wechseln signifikant positiv beeinflusst. Der Risikostrukturausgleich gleicht also Unterschiede im Gesundheitszustand nicht vollständig aus. Die komparativen Wettbewerbsvorteile der Betriebskrankenkassen werden somit über die Zeit ansteigen. Dies liefert Evidenz für das bekannte separierende Gleichgewicht von Rothschild und Stiglitz.
Keywords: C31; C35; I11; I18; 330; Health insurance choice; adverse selection; risk compensation; bivariate probit model; health production